Synthesis of ultra-high strength structured material from steam-modified delignification of wood. (1st June 2022) - Liang, Yunyi; Zheng, Guiyang; Xia, Changlei; Zuo, Shida; Ge, Shengbo; Yang, Rui; Ma, Xinxin; Fei, Benhua; Li, Jianzhang; Cheng, Chin Kui; Kim, Soo Young; Le, Quyet Van
Abstract: The use of green and renewable raw materials sourced from bio-resources is becoming more urgent to reduce the environmental pollution caused by synthetic materials such as plastics and synthetic fibers. In this work, the hydrogen peroxide (H2 O2 )/Acetic acid (HAc) steam was employed for delignification of fast-growing wood (poplar wood) in order to produce porous material and to improve compressibility. By using this approach, the delignified wood preserved the cellulose scaffold structure after treatment. Next, a simple and green vacuum-assisted resin transfer molding (VARTM) process was applied to fabricate high-performance wood-based composites from the delignified wood and epoxy resin, named CDW/Ep. Interestingly, the CDW/Ep samples showed unprecedented high mechanical performance. For example, the tensile modulus and strength of CDW/Ep samples were raised to 10.0 GPa and 316.7 MPa, respectively, which are approximately 3 and 5 times higher than those of natural wood (NW) control samples. The flexural modulus and strength of CDW/Ep samples were measured to be 18.2 GPa and 276.8 MPa which improved 198.5% and 603.5%, respectively, compared to that of NW. Furthermore, the CDW/Ep samples presented high dimensional stability after immersing in water for 72 h, as indicated by a 55.6% reduction in water absorption compared with NW samples. In summary, the fabrication of CDW/Ep in this work could prospectively lead to the development of green structural materials. Graphical abstract: Image 1 Highlights: H2 O2 /HAc steam technology was successfully applied to delignify bulk wood. Vacuum-assisted resin transfer molding was used to fabricate wood-based composites. The composites demonstrated a significant tensile strength up to 316.74 MPa. Specific strength (232.9 MPa g −1 cm 3 ) was outperformed common structural materials. Water absorption was reduced by approximately 55.6% compared to natural wood.